2020
DOI: 10.3390/pr8030361
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polymeric Materials for Chemical Enhanced Oil Recovery

Abstract: Polymer flooding is a promising enhanced oil recovery (EOR) technique; sweeping a reservoir with a dilute polymer solution can significantly improve the overall oil recovery. In this overview, polymeric materials for enhanced oil recovery are described in general terms, with specific emphasis on desirable characteristics for the application. Application-specific properties should be considered when selecting or developing polymers for enhanced oil recovery and should be carefully evaluated. Characterization te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 142 publications
(555 reference statements)
1
71
0
1
Order By: Relevance
“…This work serves as a complementary review article to some recent publications by [ 16 , 22 , 32 , 131 , 132 ]. Based on the report presented by [ 22 ] and other modifications to obtain salinity tolerance [ 15 , 39 , 78 , 133 , 134 ], we have summarized, in detail, the concise chemistry conditions behind the application of these polymeric materials.…”
Section: Summary Of Comparisonmentioning
confidence: 97%
See 3 more Smart Citations
“…This work serves as a complementary review article to some recent publications by [ 16 , 22 , 32 , 131 , 132 ]. Based on the report presented by [ 22 ] and other modifications to obtain salinity tolerance [ 15 , 39 , 78 , 133 , 134 ], we have summarized, in detail, the concise chemistry conditions behind the application of these polymeric materials.…”
Section: Summary Of Comparisonmentioning
confidence: 97%
“…In contrast to HPAM, XG is thermally stable with good resistance to hardness and good salt compatibility. However, it is also biodegradable and has a potential plugging effect when applied in excess [ 32 ]. In regards to its biodegradability, a study by [ 33 , 34 ] has shown that salt-tolerant (aerobic and anaerobic) microorganisms can degrade XG, causing it to lose its viscosity strength.…”
Section: Polyacrylamides and Polysaccharidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, it is well‐known that reservoirs at high temperatures can promote fast, severe thermal degradation of polymer molecules. [ 75 ]…”
Section: Case Studies: Demonstrating the Design Frameworkmentioning
confidence: 99%